The Structure of Hiring Costs in Germany: Evidence from Firm‐Level Data. Issue 2 (April 2016) - Muehlemann, Samuel; Pfeifer, Harald
Abstract : This paper analyzes the structure of hiring costs of skilled workers in Germany. Using detailed and representative firm‐level data on recruitment and adaptation costs of new hires, we find that average hiring costs amount to more than 8 weeks of wage payments (€4700). The structure of hiring costs is convex, as an increase in the number of hires by 1 percent increases hiring costs by 1.3 percent. We find moderate effects of labor market institutions on the magnitude but none on the structure of hiring costs. Furthermore, we provide evidence in favor of monopsony power in the German labor market.